Peran Basir Dalam Sistem Religius-Kosmologis Upacara Tiwah Pada Masyarakat Hindu Kaharingan - Sri Kayun (Jurnal Penelitian Agama Hindu, 2026)
Studies on the Tiwah ritual among adherents of Hindu Kaharingan have been widely conducted; however, research specifically examining the role of the Basir (religious leader) in implementing the Tiwah ceremony remains limited. This study aims to analyze the forms, functions, meanings, and roles of the Basir in the execution of the Tiwah ritual. This research employs a qualitative, phenomenological approach, conducted in Palangka Raya City. Data were collected through interviews with six informants, consisting of Basir, customary leaders, and community figures, using a snowball sampling technique. Data analysis was carried out using the Miles, Huberman, and Saldana model and validated through source triangulation. The findings indicate that Tiwah constitutes a religio-cosmological system enacted through ritual stages that reflect the soul's journey toward Lewu Tatau. Functionally, Tiwah embodies religious, social, aesthetic, and didactic functions, integrated within a ceremony rich in spiritual and social values. The implementation of Tiwah conveys philosophical meanings that affirm the relationship between humans, ancestors, and Ranying Hatala. The Basir plays a crucial role as a ritual leader, sacred mediator, and custodian of cosmological knowledge, ensuring the ritual's continuity and sanctity. The role of the Basir remains recognized amid the currents of modernization, due to their position as active agents of cultural reproduction in sustaining the Hindu Kaharingan religious system. This study confirms that Tiwah is not merely a mortuary ritual but a comprehensive religious system that integrates theological, social, and cosmological dimensions within the life of the Hindu Kaharingan community.